Oesophageal adenocarcinoma cell migration and metastasis : an investigation of the scaffolding protein RACK1 as a key player and therapeutic target - Duff, Deirdre (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2017)
The incidence of oesophageal adenocarcinoma is increasing at a rapid rate in Western countries (Pennathur et al., 2013). Early oesophageal cancer is often asymptomatic and metastatic disease is common at presentation leading to poor prognosis and survival rates (Pennathur et al., 2013). RACK1 is a 36kDa scaffolding protein that interacts with a wide variety of different molecules. It is a multifunctional adaptor protein which can contribute to numerous biological processes including cell proliferation, adhesion, migration, apoptosis and protein synthesis (Adams et al., 2011). RACK1 expression is altered in a variety of cancers including those of the breast, ovary, lung and prostate. (Adams et al., 2011, Li and Xie, 2014). However prior to this PhD study, the expression and function of RACK1 in oesophageal adenocarcinoma had not been examined.
Keywords: Clinical Medicine, Ph.D.; PhD Trinity College Dublin, 2017